Māori Perspectives on Asia/New Zealand Partnerships - Hapi, Robin (He Pukenga Korero: a journal of Māori studies, 1997)
Keywords: economic aspects; fisheries; international relations; mātauranga māori; social life and customs; tāngata whenua

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

Māori as “Warriors” and “Locals” in the Private Military Industry - Bargh, Maria; Whanau, Quentin (Wicazo Sa Review, 2017)
Keywords: identity; international relations; military